2015
DOI: 10.1007/s40822-015-0035-4
|View full text |Cite
|
Sign up to set email alerts
|

A long-term mortality analysis of subsidized firms in rural areas: an empirical study in the Portuguese Alentejo region

Abstract: Studies have demonstrated that public policies to support private firms' investment have the ability to promote entrepreneurship, but the sustainability of subsidized firms has not often been analysed. This paper aims to examine this dimension specifically through evaluating the mortality of subsidized firms in the long-term. The analysis focuses on a case study of the LEADER+ Programme in the Alentejo region of Portugal. With this purpose, the paper examines the activity status (active or not active) of 154 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…In the case of Alentejo, one of the study regions of this paper, there are not many studies about the impact of LEADER Approach, but on Portugal's rural development policy in general. For this reason, the works of Santos et al [29] and Neto et al [30] are significant, in which they analyzed the subsided firm's survival and the impact of local networks of public policies such as LEADER for entrepreneurships and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Alentejo, one of the study regions of this paper, there are not many studies about the impact of LEADER Approach, but on Portugal's rural development policy in general. For this reason, the works of Santos et al [29] and Neto et al [30] are significant, in which they analyzed the subsided firm's survival and the impact of local networks of public policies such as LEADER for entrepreneurships and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…In the “best performing” LAGs, these new modes of shared decision‐making and self‐regulation between actors will tend to be more fine‐tuned over time by institutionalizing a way of working together, with the appearance of new standards of behaviour and co‐operation. These new standards tend to affect the sustainability of funded projects (Santos, Neto, & Serrano, ).…”
Section: Conclusion: What Are the Links Between Territorial Governancmentioning
confidence: 99%
“…Because Leader adopts a place-based approach, and LAGs prepare for the programme's implementation based on an analysis of local needs and with special regard to the specificity of territory in which they operate, it can be assumed that the policy tasks and measures planned by the LAGs will be well suited to the needs of the local community. Centred on a case study in the Leader Programme in the Alentejo region of Portugal, Santos et al (2016) examined the longterm survival rate of firms subsidised by public policy. Using binary choice models, they showed that the cumulative mortality rate of subsidised local firms in this region was over 20 per cent.…”
Section: Design and Implementation Of The Local Development Strategy:mentioning
confidence: 99%